2022
DOI: 10.1007/s11192-021-04260-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovering temporal scientometric knowledge in COVID-19 scholarly production

Abstract: The mapping and analysis of scientific knowledge makes it possible to identify the dynamics and/or growth of a particular field of research or to support strategic decisions related to different research entities, based on bibliometric and/or scientometric indicators. However, with the exponential growth of scientific production, a systematic and data-oriented approach to the analysis of this large set of productions becomes increasingly essential. Thus, in this work, a data-oriented methodology was proposed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The primary goal of this study is to assess the current state and hotspots in the field of nutrition and gut microbiota by examining the scientific production data set related to nutrition and gut microbiota with the goal of characterisation and understanding it in terms of scientometric indices. Based on bibliometric and/or scientometric indicators, the mapping and analysis of scientific knowledge allow the identification of the dynamics and/or expansion of a specific field of study and the support of strategic decisions related to various research institutions[ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primary goal of this study is to assess the current state and hotspots in the field of nutrition and gut microbiota by examining the scientific production data set related to nutrition and gut microbiota with the goal of characterisation and understanding it in terms of scientometric indices. Based on bibliometric and/or scientometric indicators, the mapping and analysis of scientific knowledge allow the identification of the dynamics and/or expansion of a specific field of study and the support of strategic decisions related to various research institutions[ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results of scientometric studies also show that some of them have investigated the mental and psychological effects of COVID-19 disease (Santos et al, 2022 ; Liu et al, 2022 ). A scientometric study by Liu et al ( 2022 ) showed that the most common keywords in social science research on COVID-19 are related to the field of psychology and mental health.…”
Section: Introductionmentioning
confidence: 97%
“…(Farooq et al, 2021 ; Tornberg et al, 2021 ; Zhang et al, 2020 ; Casado-Aranda et al, 2021 ). They showed that publications’ content covers a wide range of topics (Colavizza et al, 2021 ), which requires a comprehensive and in-depth approach with emphasis on different disciplines in the research on COVID-19 (Aristovnik et al, 2020 ; Santos et al, 2022 ). But, a closer look shows that scientometric studies have focused on medical aspects, and social science research has been neglected (Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…ric analyses were conducted to explore the significant effect on publication patterns resulting from the pandemic, and as the pioneer, China contributed the most publications and citations (Santos et al, 2022).…”
mentioning
confidence: 99%